Retracted: M2 Macrophage–Derived Exosomes Facilitate HCC Metastasis by Transferring αMβ2 Integrin to Tumor Cells. Issue 4 (13th April 2021) - Wu, Jindao; Gao, Wen; Tang, Qiyun; Yu, Yue; You, Wei; Wu, Zhengshan; Fan, Ye; Zhang, Long; Wu, Chen; Han, Guoyong; Zuo, Xueliang; Zhang, Yao; et al.
Abstract : Background and Aims: The development and progression of hepatocellular carcinoma (HCC) is dependent on its local microenvironment. Tumor‐associated macrophages (TAMs) are deemed a key factor for the tumor microenvironment and attribute to contribute to tumor aggressiveness. However, the detailed mechanism underlying the pro‐metastatic effect of TAMs on HCC remains undefined. Approach and Results: The present study proved that TAMs were enriched in HCC. TAMs were characterized by an M2‐polarized phenotype and accelerated the migratory potential of HCC cells in vitro and in vivo . Furthermore, we found that M2‐derived exosomes induced TAM‐mediated pro‐migratory activity. With the use of mass spectrometry, we identified that integrin, αM β2 (CD11b/CD18), was notably specific and efficient in M2 macrophage–derived exosomes (M2 exos). Blocking either CD11b and/or CD18 elicited a significant decrease in M2 exos–mediated HCC cell metastasis. Mechanistically, M2 exos mediated an intercellular transfer of the CD11b/CD18, activating the matrix metalloproteinase‐9 signaling pathway in recipient HCC cells to support tumor migration. Conclusions: Collectively, the exosome‐mediated transfer of functional CD11b/CD18 protein from TAMs to tumor cells may have the potency to boost the migratory potential of HCC cells, thus providing insights into the mechanism of tumor metastasis.